Inside out - Docter, Pete; Poehler, Amy, 1971-; Smith, Phyllis, 1951-; Kind, Richard; Giacchino, Michael (Burbank, California : Walt Disney Studios Home Entertainment, 2015)
When Riley moves from the Midwest to San Francisco, her emotions aren't sure how to navigate her new town, school, and house.
Originally released as a motion picture in 2015.
In English, French, or Spanish with optional English, French, or Spanish subtitles.
Closed-captioned.
Voices: Amy Poehler, Phyllis Smith, Richard Kind, Bill Hader, Lewis Black.
Camera, Patrick Lin ; production designer, Ralph Eggleston ; editor, Kevin Nolting ; music, Michael Giacchino.
Dolby digital 5.1, wide screen 1.85:1.
Keywords: Emotions -- Drama; Moving, Household -- Drama; Comedy films; Computer animation films; Animated films; Feature films; Fiction films; Video recordings for the hearing impaired; Comedy films; Computer animation films; Animated films; Feature films; Video recordings for the hearing impaired